Growth and Yield of Six Sugarcane Varieties (Saccharum officinarum L.) - Satriyono, Wahono; Novitasari, Adin; Setiawan, Adi; Effendi, Mokhtar; Sitindaon, David Frans Yusuf (Kadiri University - Faculty of Agriculture, 2026)
Sugarcane (Saccharum officinarum L.) is a plant that can grow on uplands and lowlands. Domestic demand for sugar continuehus to increase in line with population growth and industrial development, but domestic sugar production has not been able to meet this demand. Efforts to increase sugarcane productivity and sugar production can be optimized through adaptive, high-yielding, superior sugarcane varieties. This study revealed morphological differences among six sugarcane varieties, namely PSJT 941, PS 865, PS 862, Bululawang, PA 028, and Kidang Kencana. The results of the study indicate significant morphological differences between varieties. PS 865 exhibits superior vegetative growth with the tallest plant height (224.33 cm) and stem diameter (39.33 mm), while PA 028 demonstrates highly stable characteristics with a coefficient of variation of 4.37%, indicating suitability across various environments. PS 862 and PSJT 941 exhibited longer roots and greater fresh weight, indicating adaptability to wetter conditions. Cluster analysis grouped the six varieties into two major clusters: Cluster 1 (Bululawang, Kidang Kencana, PSJT 941, PS 862) and Cluster 2 (PS 865, PA 032), showing differences in morphological structure.